Sure It Was Predictable

Algebra Level 3

{ x 2 + 4 = y 3 + 4 x z 3 y 2 + 4 = z 3 + 4 y x 3 z 2 + 4 = x 3 + 4 z y 3 \begin{cases} x^2 + 4 = y^3 + 4x - z^3 \\ y^2 + 4 = z^3 + 4y - x^3 \\ z^2 + 4 = x^3 + 4z - y^3 \end{cases}

Let x x , y y and z z be all real numbers satisfying the system of equations above. Find the value of x ! y ! z ! x!\, y!z\, !


Notation: ! ! is the factorial notation. For example, 8 ! = 1 × 2 × 3 × × 8 8! = 1\times2\times3\times\cdots\times8 .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

The given equations can be rewritten as

{ ( x 2 ) 2 = y 3 z 3 ( y 2 ) 2 = z 3 x 3 ( z 2 ) 2 = x 3 y 3 \begin{cases} (x - 2)^{2} = y^{3} - z^{3} \\ (y - 2)^{2} = z^{3} - x^{3} \\ (z - 2)^{2} = x^{3} - y^{3}\end{cases}

Adding these 3 equations together yields ( x 2 ) 2 + ( y 2 ) 2 + ( z 2 ) 2 = 0 (x - 2)^{2} + (y - 2)^{2} + (z - 2)^{2} = 0 , the sole solution to which is ( x , y , z ) = ( 2 , 2 , 2 ) (x,y,z) = (2,2,2) , (since each of the squares, which are necessarily non-negative, must equal 0 0 ).

Thus x ! y ! z ! = 8 x!y!z! = \boxed{8} .

Edit: As Calvin notes, for completeness we need to verify that ( x , y , z ) = ( 2 , 2 , 2 ) (x,y,z) = (2,2,2) satisfies the original equations, which it does indeed.

Yes same method, but i got 2 question

  1. How can we make contradiction for x y z x \neq y \neq z

  2. Is every x x , y y , z z is always the same regarding to other problem that is similar like mine ?

Jason Chrysoprase - 4 years, 4 months ago

For completeness, we should verify that ( 2 , 2 , 2 ) (2, 2, 2) is a solution to the original equation.

You have found a necessary condition, but not shown that it is sufficient.

Calvin Lin Staff - 4 years, 4 months ago
Fidel Simanjuntak
Jan 28, 2017

{ x 2 + 4 = y 3 + 4 x z 3 y 2 + 4 = z 3 + 4 y x 3 z 2 + 4 = x 3 + 4 z y 3 \begin{cases} x^2 + 4 = y^3 + 4x - z^3 \\ y^2 + 4 = z^3 + 4y - x^3 \\ z^2 + 4 = x^3 + 4z - y^3 \end{cases}

Adding up these three equations, gives us

x ² + y ² + z ² + 12 = 4 ( x + y + z ) x² + y² + z² + 12 = 4(x+y+z) .

I did some trial and error, and have ( x , y , z ) = ( 2 , 2 , 2 ) (x,y,z) = (2,2,2) .

Hence, our final answer is 8 8 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...